Evaluation and its politics: trade unions and education reform in Greece - Anna Traianou (Education Inquiry)
The implementation of global teacher and school evaluation reform has often been contentious, in ways that differ according to national context. Teacher trade unions have frequently been active opponents of reform but their strategies and motivations have been relatively little studied. This article examines evaluation reform in Greece and the role of teacher trade unions in contesting it. It situates current collisions over policy in the context of Greek politico-administrative traditions, of past relations between unions and governments and of the austerity that followed post-2010 structural adjustment programmes. It places education policy change in the broader context of state reformation and contributes to understanding its inherent politics. Working with insights from Nicos Poulantzas, it identifies evaluation reform as a restructuring of the Greek state, where relationships between central authority and political actors such as unions have been reset, weakening the position of the latter. Drawing from interviews with union representatives, it analyses their reading of policy change and the dilemmas that faced them in responding to evaluation policies. In doing so, it points out the political role of teacher trade unions in both historical and contemporary terms while also highlighting the uncertainty of their response to evaluation reform.